EPD Congress 2014 : proceedings of a symposia sponsored by the Extraction & Processing Division (EPD) of The Minerals, Metals & Materials Society (TMS) held during TMS 2014, 143rd Annual Meeting & Exhibition, Februrary 16-20, 2014, San Diego Convention Center, San Diego, California, USA - Yurko, James A. (John Wiley & Sons, Inc., 2014)
EPD Congress is an annual collection of conference proceedings that addresses extraction and processing metallurgy. The papers in this book are drawn from symposia held at the 2014 Annual Meeting of The Minerals, Metals & Materials Society. The 2014 edition includes papers from the following four symposia:FluidizationTechnologies for the Mineral, Materials, and Energy IndustriesGeneral Recycling Materials Processing FundamentalsRecycling andSustainability Update.